THE IMPACT OF DIGITAL TECHNOLOGIES ON EMPLOYEE ENGAGEMENT: CASE STUDY OF COMPANY “A” IN SERBIA - Lukić Nikolić, Jelena (The European Journal of Applied Economics, 2023)
The rapid and progressive advancement of modern digital technologies and tools, as well as their widespread application, have changed the working environment and working conditions. As a result, many concepts, methods, practices, and activities related to employee engagement must be reconsidered and adapted to the needs of the new workplace. This paper highlights the key changes in employee engagement caused by digital technologies. Obtained results from conducted case study in one IT company from Serbia showed that modern technologies enable remote work, flexible working hours, more challenging and interesting tasks, but also lead to a variety of challenges among which are technologically caused stress, over-reliance on technology, work-life conflict, and burnout syndrome. The findings presented in this paper can be useful for managers and leaders who want to build, improve, and nurture employee engagement in the digital age. Human resource managers also have valuable information on how to develop practices and methods for using digital technologies and tools in the best possible way, without negative effects and consequences on employee engagement.
Keywords: Digital Age; Digital Business; For-profit Organizations; Remote Work; Human Resources